IMPLEMENTATION OF THE ADDIE MODEL LEARNING STRATEGY IN LIFE SKILLS EDUCATION PACKET C (National High School Equivalency Examination) AT SPNF AND SKB IN TEGAL REGENCY - Muflianah, Eli (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2022)
Several learning models have been developed to enhance the curriculum of gifted students and improve their skills. This research aims to implement a learning strategy using the ADDIE model in life skills education. This approach aims to create an independent output through learning by doing, entrepreneurship, and work. The ADDIE model involves Analysis, Design, Development, Implementation, and Evaluation. The results of the study indicate that all success indicators are still being developed in terms of quality and quantity. The development is tailored to educational institutions that provide life skills education, ensuring that everything runs smoothly during the learning process. Therefore, the indicators of success are developed by adding or improving the relevant aspects.